ANALYSIS OF THE MEANING OF THE EXPRESSION OF HOHO SINGING AT THE TRADITIONAL DEATH CEREMONY OF THE SOUTHERN NIAS COMMUNITY THROUGH SEMIOTIC APPROACH - Trinitatis Fau; Intama J. Polii; Nontje Pangemanan (Faculty of Language and Arts (Fakultas Bahasa dan Seni) Universitas Negeri Manado, 2023)
This research aims to describe the meaning of Hoho singing phrases associated with the traditional death ceremony of the South Nias community through Peirce's semiotic approach. A qualitative approach with a focus on musicology was used as the research method. Data was collected through observation, interviews and documentation. The results revealed that the Hoho is performed by a minimum of 5 people in the group presenting the text, with a leader from the si'ulu or si'ila group called sondroro or Hoho Participant. The Hoho is also responded to in turn by several small groups of two to four text presenters known as sanoyohi or Speakers. All Hoho presenters are male. Textual analysis of the meaning and message of the Hoho shows that Lawaendröna is looking for a way out of the threat of death. He considers various possibilities, including going to the moon, but eventually realizes that humans cannot escape death. In essence, the Hoho depicts the human life cycle and philosophical questions about death and eternity.